Storage Layout on Spring Company using Shared Storage and Analysis Market Basket - rifky maulana yusron; emon rifai'i (Universitas Trunojoyo Madura, 2019)
Spring manufacturing company has finished goods warehouse, some storage area using manufacturing near-net-shape product. In observations made on finished goods warehouse for preparation and arrangement of product is less neat, especially on layout of a storage area in near-net-shape warehouse, resulting in slow arrangement of products, slow process of servicing the product, slow delivery of product, and a waste of space in finished goods warehouse. The aim of this study is to provide proposed improvements near-net-shape warehouse layout with a combination of two methods, namely shared storage and market basket analysis. Function of both make finished goods warehouse layout that takes into account consumer demand for products most in demand will be placed closest to warehouse door, and products that are often purchased together will be brought closer. Result of a combination of shared storage methods and market basket analysis can minimize mileage material handling, minimizing setup time, and service, so process becomes smooth delivery and avoid delays. Results from this study are shaped layout proposals are made based on calculation of shared storage methods and market basket analysis, so that layout products previously still unregulated to regulated, and service will be faster with placement of frequently purchased products and products that are frequently purchased simultaneously when placed at front. Products are placed in front of, among others. The most frequently purchased products BLS with 10.756 products and lowest purchased are K59 with 920 products